The influence of fish cage aquaculture on pelagic carbon flow and water chemistry in tidally dominated mangrove estuaries of peninsular Malaysia - Alongi, D.M.; Chong, V.C.; Dixon, P.; Sasekumar, A.; Tirendi, F. (Elsevier, 2003)
The impact of floating net cages culturing the seabass, Lates calcarifer, on planktonic processes and water chemistry in two heavily used mangrove estuaries in Malaysia was examined. Concentrations of dissolved inorganic and particulate nutrients were usually greater in cage vs. adjacent (≈100 m) non-cage waters, although most variability in water-column chemistry related to water depth and tides. There were few consistent differences in plankton abundance, production or respiration between cage and non-cage sites. Rates of primary production were low compared with rates of pelagic mineralization reflecting high suspended loads coupled with large inputs of organic matter from mangrove forests, fishing villages, fish cages, pig farms and other industries within the catchment. Our preliminary sampling did not reveal any large-scale eutrophication due to the cages. A crude estimate of the contribution of fish cage inputs to the estuaries shows that fish cages contribute only ≈2% of C but greater percentages of N (32–36%) and P (83–99%) to these waters relative to phytoplankton and mangrove inputs. Isolating and detecting impacts of cage culture in such heavily used waterways—a situation typical of most mangrove estuaries in Southeast Asia—are constrained by a background of large, highly variable fluxes of organic material derived from extensive mangrove forests and other human activities.